2020
DOI: 10.1186/s12884-020-03031-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and factors associated with antenatal, delivery and postnatal Care Services in Tigray Region, Ethiopia: a community-based cross-sectional study

Abstract: Background: This study aimed to identify the utilization and factors associated with antenatal care, delivery, and postnatal care services in Tigray regional state, Ethiopia. Methods: A community-based cross-sectional study was conducted among 667 women of reproductive age group who had children aged 45 days-6 months in 13 districts (3 urban and 10 rural). Data were collected from May-June 2015. Multistage sampling technique was used. The data were analyzed using SPSS version 20. Multiple variable logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
3
8
1
Order By: Relevance
“…ANC visits as per the MOH recommendation consistently increases the likelihood of uptake of CoC across all hypothesis testing models. Previous studies showed that higher number of ANC visits are associated with increased uptake of MHS (37,38). When those contacts are at the recommended type of HFs, it improves the continuity of maternity care (39).…”
Section: Discussionmentioning
confidence: 95%
“…ANC visits as per the MOH recommendation consistently increases the likelihood of uptake of CoC across all hypothesis testing models. Previous studies showed that higher number of ANC visits are associated with increased uptake of MHS (37,38). When those contacts are at the recommended type of HFs, it improves the continuity of maternity care (39).…”
Section: Discussionmentioning
confidence: 95%
“…ANC visits as per the MOH recommendation consistently increases the likelihood of uptake of CoC across all hypothesis testing models. Previous studies showed that higher number of ANC visits are associated with increased uptake of MHS [ 38 , 39 ]. When those contacts are at the recommended type of HFs, it improves the continuity of maternity care [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, though the government expanded access to facilities and free ambulance transport, the country has poor road access, difficult terrain, and roads that are often unreachable during the rainy season. A recent study in Ethiopia affirms that women living in remote areas with no access to transportation did not have access to maternal health services [43]. This might discourage women to visit the facility for skilled birth, particularly during the night time and rainy season.…”
Section: Plos Onementioning
confidence: 99%